Capacidade burocrática no Brasil e na Argentina: Quando a política faz a diferença - Celina Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The study analyses bureaucratic capacity in Brazil's and Argentina's federal governments by applying the concept of state capacity. To capture the capacity civil servants the study investigated dimensions such as professionalization, qualification, promotion rules, and recruitment mechanisms for entering the civil service. The study shows that although both countries experienced the same trajectory in the early years of the construction of their bureaucratic systems and that access to civil service combined patronage and meritocratic patterns in the early 2000s, however, Brazilian political elites implemented a constitutional mandate determining that access to civil service was conditioned to competitive exams, making the system closer to Weber's rational-legal authority type. Argentina, in contrast, kept the selection of their civil servants based on personal and political ties. This does not mean that Argentina's bureaucracy lacks quality but they do not fulfill some of Weber's requirements such as stability and selection more based on merit rather than patronage. The study argues this difference is explained by different redemocratization agendas.
Keywords: O29; 330; bureaucratic capacity; burocratization; redemocratizarion; Argentina; Brazil